Perspectives for the future. Challenges and opportunities in Peru’s cultural diversity - Benamar Daoudi, Ilyass (REVISTA ELECTRONICA IBEROAMERICANA, 2025)
Peru, located in the center of South America, offers a unique experience thanks to its natural diversity and rich cultural heritage, ranging from the Andes Mountains to the Amazon jungles. The Andes Mountains, besides being a group of mountains and a natural border, are a symbol of the rich history and culture of the country, being considered sacred by ancient civilizations such as the Incas. In Peruvian communities, agricultural life, textile craftsmanship and deep-rooted customs stand out, which have shaped the artistic panorama and given rise to a mestizo culture, reflected in art, literature and contemporary society. In the following sections, we have explored the diverse cultural narratives that shape Peruvian identity, and how they are reflected in art, music and traditions. The importance of preserving cultural heritage and promoting responsible tourism that respects and values the country’s diversity has also been analyzed.